Nordic walking for geriatric rehabilitation: a randomized pilot trial. (June 2013) - Figueiredo, Sabrina; Finch, Lois; Mai, Jiali; Ahmed, Sara; Huang, Allen; Mayo, Nancy E.
<x xml:space="preserve">Abstract</x> Purpose: There is a need to identify effective interventions to promote walking capacity in seniors. This study compares nordic walking (NW) and usual overground walking (OW) and estimates the relative efficacy in improving walking capacity (endurance and gait speed) of the elderly. Method: Single blind, site-stratified, randomized, pilot trial designed to estimate the amount of change with NW and OW. Main outcomes were distance walked measured by 6-min walk test (6MWT) and comfortable gait speed measured by 5-meter walk test (5MWT). Explanatory variables were age, sex, number of comorbidities, walking aids, balance, pain, and leg function. Results: NW and OW participants improved, respectively, 45 and 41 m on 6MWT and increased their gait speed by 0.14 and 0.07 m/s, respectively. NW effect sizes were moderate for 6MWT (ES = 0.53) and large for gait speed (effect size (ES) = 0.68). OW demonstrated moderate effect size for 6MWT (ES = 0.53) but a small one for gait speed (ES = 0.33). Relative efficacy, which was obtained from the ratio of NW and OW effects' sizes, was 1 for 6MWT and 2.06 for gait speed. Conclusions: NW is 106% more effective in improving gait speed among elderly than OW.